Analisis Perbandingan Laba UMKM Sebelum dan Sesudah Menggunakan QRIS (Studi Kasus Pada: UMKM Kuliner Bandar Lampung) - Rahel Raneta Sirait; Haninun Haninun; Khairudin Khairudin (Journal of Education Transportation and Business, 2024)
The very rapid development of technology can be seen from the large number of people who use technology in everyday life. The presence of non-cash payments such as QRIS can increase efficiency in managing the finances of a business but can also increase the profits of a business. The use of QRIS is increasingly being used by MSMEs, there are various promotions carried out, as well as various other factors that can influence the success of MSMEs because it increases efficiency (ease) in transactions and makes it easier for MSMEs to carry out buying and selling transactions and book keeping their finances. This research aims to determine the comparison of MSME profits before and after using QRIS in Bandar Lampung Culinary MSMEs, so it is classified as associative or relationship research, namely research to determine cause and effect, using quantitative research methods. The data in this research was obtained using a questionnaire distributed to 30 culinary MSMEs using QRIS in Bandar Lampung City. To analyze the data, the SPSS application was used. The results of this research showed that there were differences in MSME profits before and after using QRIS in Bandar Lampung Culinary MSMEs. This was concluded based on the independent t test. It can be seen that the significance value is smaller than 0.05 (0.001 0.05). In this research, the significance value is smaller than the stipulated significance value, namely 0.05, so we accept the hypothesis, namely that there is a difference in MSME profits before and after using QRIS in Bandar Lampung Culinary MSMEs.